The formation of historical sense - Padilla, Juan (Pensamiento. Revista de Investigación e Información Filosófica, 2022)
The aim of this article is to describe how has been formed in the West the historical sense as we know it today, that is to say how has been developed the sense by which we perceive in everything that surrounds us its past, its origin, the history by which it has come to be what it is. The acquisition of this sense has been a slow, laborious and uneven process, the result of multiple contributions and enrichments. Like all the other senses, the historical sense needs to be educated and cultivated, because what has been achieved with difficulty can easily be ruined.